AB0661 Mortality in patients with systemic lupus erythematosus in a single centre in singapore. (23rd January 2014) - Chia, F.L.; Thong, B.Y.H.; Kong, K.O.; Howe, H.S.
Abstract : Background: SLE is associated with an increased risk of death compared to the general population. Survival in SLE patients has improved significantly over the last 20 years with a decrease in active SLE as a cause of early death and an increase in late deaths due to atherosclerotic events and malignancy. Causes of death have not been described in an oriental cohort of this size thus far. Objectives: To study the causes of death in patients with SLE prospectively followed up from 2002 to 2011 in a single tertiary centre in Singapore. Methods: The cohort consists of 1013 patients who fulfill the American College of Rheumatology 1982 revised criteria for SLE. 222 patients had early disease (<3 years) and 791 patients had late disease (≥3 years). We examined the data on patients from the cohort who had died during follow up and compared them with results from a previous study from our centre published in 1997. Results: 74 patients (7.3% of cohort) with SLE died during the follow up period. 68 (91.8%) were female and 6 (8.1%) were male. Mean age at diagnosis was 38.7 years (range 9.7-68 years). Mean age at death was 52.3±13.0 years (range 17.5–74.3 years). Mean duration of disease was 14.1±9.0 years (range 0-36.9 years). Infection was the most common cause of death in 25 (33.8%) patients, followed by acute vascular events (10, 13.5%), malignancy (8, 10.8%), sudden death (6, 8.1%), active SLE (5, 6.8%), pulmonary hypertension (5, 6.8%), suicide (1, 1.4%) and others (6, 8.1%). Cause of death was not available for 8 patients. Three patients (4.1%) died within the first 3 years of diagnosis: 1 from active SLE and 2 from non-SLE related disease. Organ involvement in the 5 patients who died of active SLE were as follows; lupus nephritis (5), cerebral lupus (4), pancytopaenia (2), pulmonary haemorrhage(2) and thrombotic thrombocytopaenic purpura(1). The major sites of infection were pulmonary (56%), urinary tract (12%), intra-abdominal (12%) and skin (8%). One patient died from acquired immunodeficiency syndrome and 1 patient had progressive multifocal leucoencephalopathy. Five patients (20%) who died from infection had end-stage renal failure and 4 (16%) had malignancy. Deaths from vascular events comprised 5 (50%) cerebral haemorrhage, and 5 (50%) myocardial infarction, among whom 6 (60%) patients had APS and 5 (50%) were on anticoagulation. Deaths from malignancy were all from solid organ carcinomas, the most common being CA Lung. Thd median steroid dose at the last prescription prior to death was 8±29.4mg/day of prednisolone. Compared to the previous study describing mortality from the same centre in the 1990s, the percentage of patients who had SLE flare as a cause of death dropped from 44.8% to 6.8% (p<0.01). Acute vascular events and malignancies are also significant contributors in contrast to no cases then. Average age of death has risen from 35.1 to 52.3 years (p<0.01). Conclusions: Although death from active SLE has diminished in the last 15 years, infection remains the leading cause of death. References: Ippolito A, Petri M. An update on mortality in Systemic lupus erythematosus. Clin Exp Rheumatol 2008; 26 (Suppl. 51):S72-S79. Koh ET, Seow A, Leong KH, Chng HH SLE mortality in an oriental population. Lupus. 1997;6(1):27-31. Disclosure of Interest: None Declared